Tactile identification of textures using machine learning/ deep learning - Goh, Jun Bin (Nanyang Technological University, 2022)
In the recent years, Artificial Intelligence technology has grown exponentially, especially in sub-areas such as Machine Learning and Deep Learning. However, many of its applications rely on image acquisition techniques to obtain datasets. This project seeks to establish a method to identify an object, based on its haptic properties, and using Machine Learning and/or Deep Learning techniques.